The Role of Cue-Based Strategies in Skilled Diagnosis Among Pathologists. (November 2022) - Carrigan, Ann J.; Charlton, Amanda; Foucar, Elliott; Wiggins, Mark W.; Georgiou, Andrew; Palmeri, Thomas J.; Curby, Kim M.
Objective: This research was designed to test whether behavioral indicators of pathology-related cue utilization were associated with performance on a diagnostic task. Background: Across many domains, including pathology, successful diagnosis depends on pattern recognition that is supported by associations in memory in the form of cues. Previous studies have focused on the specific information or knowledge on which medical image expertise relies. The target in this study is the more general ability to identify and interpret relevant information. Method: Data were collected from 54 histopathologists in both conference and online settings. The participants completed a pathology edition of the Expert Intensive Skills Evaluation 2.0 (EXPERTise 2.0) to establish behavioral indicators of context-related cue utilization. They also completed a separate diagnostic task designed to examine related diagnostic skills. Results: Behavioral indicators of higher or lower cue utilization were based on the participants' performance across five tasks. Accounting for the number of cases reported per year, higher cue utilization was associated with greater accuracy on the diagnostic task. A post hoc analysis suggested that higher cue utilization may be associated with a greater capacity to recognize low prevalence cases. Conclusion: This study provides support for the role of cue utilization in the development and maintenance of skilled diagnosis amongst pathologists. Application: Pathologist training needs to be structured to ensure that learners have the opportunity to form cue-based strategies and associations in memory, especially for less commonly seen diseases.